Wittgenstein: la filosofía como phármakon del encantamiento del lenguaje - Ruano de la Fuente, Yolanda (Logos. Anales del Seminario de Metafísica, 2002)
The purpose of this article is to explore the concept of Philosophy within the works written by Wittgenstein if we take into account the ambivalent sense of the term phármakon. Thus, it will be outlined a contest of paradoxes between, on the one hand, healthiness, sanity, and the adaptable confidence produced by western rationality materialized into objective science, and, on the other hand, sickness, insanity, the world of perplexities, and the realm of desire and death, essential to philosophical thought. Bearing in mind last Wittgenstein’s approaches, we will understand the Tractatus both critical to the deficiencies of western Reason and imprisoned within them. But the “enchanting” power of western Reason, conducting to identify rationality and scientificity in that work, will be conjured in the last Wittgenstein through the opening of plural realms of rationality and of discourses. In this way, philosophical questions will be rescued from silence and absurdity.